Financial Analysis of The Anchovies Purse Seiner Vesel Bisuness Based in Larangan Coastal Fishing Port Tegal Regency - Haris, Dendi; Mulyani, Sri; Kusnandar, Kusnandar; Wera, Agung Ferdinand; Sutono Hs, Dian; Suratna, Suratna (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
The Larangan Coastal Fishing Port (Larangan CFP) is the only fishing port in the administrative area of Tegal Regency, as a quite productive fish landing center and is the catch of fishermen operating in the coastal watiers of Tegal with anchovy main commodity. Because it is one of the fishing tools of the fishing community which is classified as productive and is based in the Larangan CFP. is the type of anchovies surrounding net (purse seine) In this study, 8 units of purse seiners were selected using light capture device (lamp) as samples, using case study and observation/interview metods and financial analysis which include; Profit and Loss, Payback Period, B/C Ratio, BEP, NPV, IRR and Swiching Value. From the calculation results of the economic (financial) analysis of fishing activities with purse seine anchovies based at the Larangan CFP, Tegal Regency is general can be categorized as feasible, because all business feasibility indicators are still above the required criteria as a feasible business activity to run. The avarage value of each of these indicators is; Paybac Period (4.4 years or 4 years 3 months), Break Even Point (Rp.202,168,749), B/C Ratio (1.24), NPV (Rp.325,474,008), and IRR (22%). Then the replacement value (Switching Value) also still sows a business that is feasible continuimg with an average B/C Ratio of 1.20 and a Payback Period of 5.2 years with the analysis of two scenarios of each situation; 3% for a decrease in production value, and 3.5% for an increase in input prices.